-6x+28=5x-12

Simple and best practice solution for -6x+28=5x-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x+28=5x-12 equation:


Simplifying
-6x + 28 = 5x + -12

Reorder the terms:
28 + -6x = 5x + -12

Reorder the terms:
28 + -6x = -12 + 5x

Solving
28 + -6x = -12 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
28 + -6x + -5x = -12 + 5x + -5x

Combine like terms: -6x + -5x = -11x
28 + -11x = -12 + 5x + -5x

Combine like terms: 5x + -5x = 0
28 + -11x = -12 + 0
28 + -11x = -12

Add '-28' to each side of the equation.
28 + -28 + -11x = -12 + -28

Combine like terms: 28 + -28 = 0
0 + -11x = -12 + -28
-11x = -12 + -28

Combine like terms: -12 + -28 = -40
-11x = -40

Divide each side by '-11'.
x = 3.636363636

Simplifying
x = 3.636363636

See similar equations:

| x/8=35/56 | | 5+40=40 | | b/15=26/30 | | 12x+4=10x-8 | | 7/2a=/10ab^3 | | x/5=200/25 | | 71+(-5*x+(-2*x+3))=25-(-(3*x+4)-(4*x+3)) | | lnx+lnx=3 | | -5n-8(1+7x)=-8 | | 9(8X+11)=135 | | 7x-16=4(x-3) | | 71+(-5*x+(2*x+3))=25-(-(3*x+4)-(4*x+3)) | | 2(2n-5)=-6n+14+4n | | 22x-35=2x+5 | | x=1.666666667+-3y | | 10+-3x+8x=25 | | 7(1-2x)=-2-5x | | 11/9=y/81 | | -6(-7n-7)=-30+6n | | 2*3y+4y=10 | | 4x+x+-15+3+-8x=13 | | 3a-b=-9 | | 6(8+6v)+7v=134 | | 10=-x+3x^2 | | 6x+-14x+16=-35+11 | | 14/3=a/15 | | 8x+25=321 | | 3(2+6x)=12 | | -3(2x-3)=5x | | 9+3x+x=1 | | 8(7+5n)=256 | | -5x-2=-2x+10 |

Equations solver categories